Efficiency optimization of a direct torque control (DTC) induction motor drive - Sim, Sy Yi (2016)
Typical Direct Torque Control (DTC) Induction Motor (IM) drive has good efficiencies while operating at its rated condition. Nevertheless, a motor drive operates far from its rated operating condition, which impairs the efficiency. Therefore, a conventional DTC IM drive system should be associated with a loss minimization strategy to maximize the drive efficiency for a wider range of operation. For a given operating condition, the losses in an IM can be minimized by adjusting to the appropriate flux level instead of conventionally keeping constant at its rated flux value. Consequently, this research proposed an online learning Artificial Neural Network Efficiency Optimization (ANNEO) controller with the aim to generate an adaptive flux level to optimize the efficiency of any different operating points, especially at low speed and low torque condition. ANNEO is implemented with an online learning second order Levernberg-Marquardt algorithm. The proposed controller uses the input power of the drive system as the objective function and minimizes it. In order to further improve the system dynamic response, an Artificial Neural Network speed controller (ANNSC) of DTC is included. In ANNSC, the back propagation algorithm is employed. The goal of this research is to achieve the efficiency optimization of DTC induction motor drives system while preserve the superior speed performance of IM application over a wide speed range. The entire DTC drive system along with the proposed adaptive flux ANN based controller has been modeled in Simulink/Matlab and validated experimentally by the ControlDesk 5.1 with dSPACE DS1103 Real-time Digital Signal Controller. An efficiency improvement as high as 14.6% and 12.75% have achieved for simulation and experimental testing respectively at low speed and low load condition. The simulation and experimental results show that the proposed technique managed to generate adaptive optimum flux level, hence improves the efficiency of the DTC induction motor drive system while at the same time, preserving excellent speed performance of the systems.